Could “Sub-RPE Illumination” be a prognostic marker for dry AMD? - Yozgat, Zübeyir; Işık, Mehmed Uğur; İlgüy, Serdar; Ece, Berire Şeyma Durmuş; Sabaner, Mehmet Cem (Research Square Platform LLC, 2023)
Abstract
Purpose To evaluate the natural history of dry aged related macular degeneration (AMD) with advanced retina pigment epithelium (RPE) analysis and sub-RPE illumination (SRI) data and to determine its relationship with progression. Methods Fifty-four eyes of 54 patients with dry AMD who presented with visual symptoms were included in this longitudinal study. SD-OCT scanning was used to evaluate central macular thickness (CMT), average central retinal thickness (CRT), foveal outer nuclear layer (ONL) thickness, ellipsoid zone (EZ) integrity. Advanced RPE analysis software was used for area and volume data at 3mm and 5mm, and SRI assessment at 5mm circles. Results This study consisted of 54 patients (29 female) aged 74.72 ± 8.38 years. Area in 3 mm and 5 mm circles (mm²), volume in 3 mm and 5 mm circles (mm³) were found increased at final visit (all, p < 0.001). In SRI data, area in 5 mm circle (mm²) was found to be higher at the final visit (p < 0.001). CMT, CRT, and ONL thickness data were found decreased at final visit (p = 0.014, p < 0.001, p < 0.001, respectively). Baseline and final LogMAR were found decreases inversely as the distance of SRI to the fovea increases (p: 0.03, r = -0.347 and p: 0.04, r= -0.382, respectively). Baseline SRI was higher in patients with disintegrity of EZ at the onset [0.8 (0.1–1.19) vs 0.0 (0–0.1), p: 0.002]. In addition, those with initial disintegrity of EZ had higher final SRI than those without [1.1 (0.3–2.1) vs 0.1 (0.1–0.2), p : 0.038]. There was a significant positive correlation between initial SRI area and final LogMAR (p < 0.001, r = 0.645). Conclusion Initial SRI area could predict the risk of vision loss at the end of the 12-month follow-up, and SRI could be considered as a predictor for dry AMD progression.